Social Network Analysis in Transnational Settings: The Case of Mexico City's AIDS CBOs - Nielan Barnes (Social Medicine Publication Group, 2010)
Using a case study approach, I show how transnational civil society networks both help and hinder community-based HIV/AIDS organizations by providing opportunities for community-state partnerships that favor some local organizations over others, and (re)produce intra-organizational stratification at the local level. In the case of Mexico City, transnational ties encourage community-based AIDS organizations to develop formal organizational forms and strategies (negotiating fronts) which often enhance organizational sustainability and draw organizations into a closer relationship with the state institutionalized sphere. However, such ties also create divisions (political fronts) between outsider and insider organizations that compromise local inter-organizational collaboration and service delivery. As a result, transnational networks and resources solidify outsider-insider conflicts and balkanize service provision along political lines. The conclusions of this research are helpful to international health practitioners and social scientists seeking to understand how transnational networks and resources shape global civil society, and can both challenge and reproduce existing community-state power regimes and health inequities at local and transnational levels.